V All-Russian scientific and practical conference “Actual issues of physical education of youth and student sports” - Brilenok, Nailya B. (Физическое воспитание и студенческий спорт, 2022)
The article presents a report on the V All-Russians scientific and practical conference “Actual issues of physical education of youth and student sports”, held on May 17–18, 2022 on the basis of the Saratov National Research State University named after N. G. Chernyshevsky.